Case report: Conjunctival melanoma treated with relatlimab and nivolumab showing remarkable response - Attrash, Mirona; Badran, Omar; Shapira, Yinon; Bar-Sela, Gil (Frontiers in Oncology, 2024)
Conjunctival melanoma, an uncommon form of ocular melanoma, shares some molecular characteristics with cutaneous melanoma and some with mucosal melanoma. Treatment of cases where it becomes advanced or metastatic raises unique treatment challenges. Nivolumab/relatlimab (Opdualag) recently received FDA approval for metastatic melanoma based on the phase 2/3 RELATIVITY-047 trial, which showed better median progression-free survival (PFS) in the first-line setting without new safety signals. The efficacy of this drug in conjunctival melanoma has not been reported yet.Case presentationAn 87-year-old woman with a history of mild dementia was admitted to the oncology department with a large, exophytic tumor protruding from her left eye, diagnosed as conjunctival melanoma two years previously. This tumor was secreting a whitish fluid and obstructing her vision. Immunotherapy with Opdualag was started, with a near clinical complete response after the 1st cycle. The patient was treated with only four cycles due to worsening of her dementia.ConclusionNivolumab/relatlimab (Opdualag) is a promising treatment alternative in conjunctival melanoma when surgery is not viable.